Sistem Informasi Pelayanan Dan Pengolahan Data Bengkel Berbasis Web (Studi Kasus : Bengkel Izul) - Nur, Ahmad Fadlan (Journal of Computer Science and Information System(JCoInS), 2022)
Izul Workshop is one of the workshops established since 2000, Izul's workshop provides suferpat, and special motorcycle service. Along with the times, business competition is also increasingly rapid in the automotive world, where this competition requires business people to maximize business performance in order to compete in the automotive market. The entrepreneur must be able to work hard to learn and understand the needs and desires of customers in order to improve the image of the workshop in the eyes of the public. For nearly 18 years standing in the hamlet of the central village, and to overcome the problems of customers from outside the village of the central village, Izul Motor's workshop maximized its performance in filing complaints from customers. However, ordering and data collection of items is still done manually by recording all data and goods sold using books so that it is less efficient. To overcome this we need an application that can facilitate the data collection of goods and ordering goods using Mysql, php. The results of the design of this application in the form of registering orders and data collection web-based goods.